Pengembangan Kurikulum BIPA di Jurusan Tadris Bahasa Indonesia - Mulyaningsih, Indrya (ppjbsip, 2022)
The existence of the BIPA Institute at IAIN Syekh Nurjati Cirebon will also influence higher education accreditation. One component of the BIPA Institute is the curriculum. This research aims to develop the BIPA curriculum in the Indonesian Language Tadris Department. This qualitative research uses descriptive methods. Data was obtained through observation, interviews, and documentation from the BIPA Institute at IAIN Surakarta, IAIN Tulungagung, Yogyakarta State University, and Sebelas Maret University Surakarta. Data were analyzed using the steps of collection, presentation, reduction and drawing conclusions. Validity of data using triangulation: theory, time, sources, methods, and researchers. The research results show that the development curriculum: 1) is new to planning, 2) pays attention to learner needs, 3) uses culture as media and material in learning, and 4) needs to receive support for facilities and infrastructure from IAIN Syekh Nurjati Cirebon.AbstrakKeberadaan Lembaga BIPA di IAIN Syekh Nurjati Cirebon akan turut memengaruhi akreditasi Perguruan Tinggi. Salah satu komponen Lembaga BIPA adalah kurikulum. Penelitian ini bertujuan untuk mengembangan kurikulum BIPA di Jurusan Tadris Bahasa Indonesia. Penelitian kualitatif ini menggunakan metode deskriptif. Data diperoleh melalui observasi, wawancara, dan dokumentasi dari Lembaga BIPA di IAIN Surakarta, IAIN Tulungagung, Universitas Negeri Yogyakarta, dan Universitas Sebelas Maret Surakarta. Data dianalisis menggunakan langkah pengumpulan, penyajian, reduksi, dan penarikan simpulan. Keabsahan data menggunakan triangulasi: teori, waktu, sumber, metode, dan peneliti. Hasil penelitian menunjukkan bahwa pengembangan kurikulum: 1) baru pada perencanaan, 2) memperhatikan kebutuhan pemelajar, 3) menggunakan budaya sebagai media dan materi dalam belajar, serta 4) perlu mendapat dukungan sarana dan prasarana dari IAIN Syekh Nurjati Cirebon.